A Nation-Wide Survey of High School Baseball Coaches’ Perceptions Indicates their Arm Care Programs Play a Role in Injury Prevention - K A Matsel; E E Weiss; R J Butler; M C Hoch; P M Westgate; T R Malone; T L Uhl (International Journal of Sports Physical Therapy)
# Background